Results from the Intra-Hospital Commission for Organ and Tissue Donation for Transplantation (CIHDOTT) at Hospital Cristo Redentor in Porto Alegre - Marques, Sue Helen Barreto; Cézaro, Paula De; Soares, Danieli Cerri; Azeredo, Nára Selaimen Gaertner de (Brazilian Journal of Transplantation, 2007)
Organ donation has always been a controversial issue. When transplantation became steady, its higher limiting factor arose from the organ scarceness. The organs and tissues removal can only take place after the encephalic death diagnosis, defined as the complete and irreversible stop of encephalic functions. In order to speed up the organ procurement and donation process, Intra-Hospital Commissions for Organ and Tissue Donation for Transplant (CIHDOTT) have been established by the Decree no. 1.262 of June 16, 2006. Hospital Cristo Redentor (HCR), a reference in trauma and neurology has one of the biggest organ procurement organ rates in the state Rio Grande do Sul. Purposes: The purpose of this paper is to present data concerning the procurement at HCR. Methods: Data were collected since 2005. There is no confirmed registration evidencing procurement in previous years. Results: In the first semester of 2005, only 9.2% families of patients who died were approached to donate. During the second semester, 10.3% families were approached, followed by 19.6% and 39.1% in the first and second semester of 2006, respectively. In the first semester of 2007, 26.6% families were approached by the CIHDOTT, and 33.8% in the second semester of that same year. Conclusions: From the CIHDOTT implantation, it is perceived an increase in the approach of families for the corneas and multiple organs procurement. Such finding discloses that despite its recent activity, the HCR CIHDOTT Commission performance is successful in a significant way.